Non-cell-autonomous Neurotoxicity of α-synuclein Through Microglial Toll-like Receptor 2 - Kim, Changyoun (Exp Neurobiol, 2016)
Synucleinopathies are a collection of neurological diseases that are characterized by deposition of α-synuclein aggregates in neurons and glia. These diseases include Parkinson's disease (PD), dementia with Lewy bodies, and multiple system atrophy. Although it has been increasingly clear that α-synuclein is implicated in the pathogenesis of PD and other synucleinopathies, the precise mechanism underlying the disease process remains to be unraveled. The past studies on how α-synuclein exerts pathogenic actions have focused on its direct, cell-autonomous neurotoxic effects. However, recent findings suggested that there might be indirect, non-cell-autonomous pathways, perhaps through the changes in glial cells, for the pathogenic actions of this protein. Here, we present evidence that α-synuclein can cause neurodegeneration through a non-cell-autonomous manner. We show that α-synuclein can be secreted from neurons and induces inflammatory responses in microglia, which in turn secreted neurotoxic agents into the media causing neurodegeneration. The neurotoxic response of microglia was mediated by activation of toll-like receptor 2 (TLR2), a receptor for neuron-derived α-synuclein. This work suggests that TLR2 is the key molecule that mediates non-cell-autonomous neurotoxic effects of α-synuclein, hence a candidate for the therapeutic target.